X-ray Photoelectron Spectroscopy Analysis and Electrical Properties of Bi0.5(Na0.80K0.20)0.5TiO3-LiNbO3Lead-Free Piezoelectrics - Pimpilai Wannasut (2018)
© 2015 Copyright Taylor and Francis Group, LLC. Lead-free piezoelectric ceramics with formula of (1-x)Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -xLiNbO 3 or (1-x)BNKT-xLN (when x=0, 0.005, 0.010, 0.015 and 0.020 mol fraction) were produced by a solid-state mixed oxide method. The ceramics with density ranging 5.38 -5.68 g/cm 3 were obtained by sintering at 1100°C. X-ray diffraction pattern showed that (1-x)BNKT-xLN ceramics exhibited pure perovskite structure. X-ray photoelectron spectroscopy analysis was used to identify of chemical composition, chemical state and binding energy of ionic species in the ceramics. Dielectric, ferroelectric and piezoelectric properties of all ceramics were investigated and found to be optimized at the composition of x=0.005.